Pertentangan Kelas Dalam Novel Bumi Manusia Karya Pramoedya Ananta Toer - Hatibie, Yunita (Reduplikasi: Jurnal Penelitian Pendidikan Bahasa Indonesia, 2024)
Literary works are the creation of human works that are written using beautiful language and have aesthetic value and are able to attract the attention of readers to enjoy with taste and hope. Bumi Manusia is one of the novels by Pramoedya that records the historical journey of the Indonesian nation in the early 20th century. This study aims to find out and provide an in-depth scientific explanation of Class Conflict in the Novel Bumi Manusia by Pramoedya Ananta Toer. This study uses a qualitative method with content analysis techniques. The approach used is genetic structuralism. The figures in Bumi Manusia are structuralism as a symbol of the social classes in Indonesian society. The figures who represented the social classes were Maurits Mellema who represented the ruling class, Minke who represented the intellectual class, Babah Ah Tjong who represented the East Asian class (Traders), and Nyai Ontosorh who represented the common people. Five forms of class conflict that occur in Indonesia according to the description of the structure of the Human Earth. The conflict is between intellectuals and nobles who in the text are described through the figures of Minke and the Regent, between the intellectuals and the rulers who are described through Minke and Maurits Mellema, the common people and ethnic Chinese who are described through Nyai Ontosoroh and Babah Ah Tjong, the people and rulers who are described through Nyai Ontosoroh and Maurits Mellema, and the intellectuals who are described through Minke and his brother Minke and Robert Suurhof.